2007
DOI: 10.1016/j.atherosclerosis.2006.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Associations between HDL-cholesterol and polymorphisms in hepatic lipase and lipoprotein lipase genes are modified by dietary fat intake in African American and White adults

Abstract: Polymorphisms in genes involved in HDL-cholesterol (HDL-C) metabolism influence plasma HDL-C concentrations. We examined whether dietary fat intake modified relations between HDL-C and polymorphisms in hepatic lipase (LIPC-514C→T), cholesteryl ester transfer protein (CETP TaqIB), and lipoprotein lipase (LPL S447X) genes. Diet (food frequency questionnaire), plasma lipids, and LIPC, CETP, and LPL genotypes were assessed in ~12,000 White and African American adults. In both races and all genotypes studied, minor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
61
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 52 publications
7
61
5
Order By: Relevance
“…The human HL/LIPC gene is located on chromosome 15 (15q21). Several HL/LIPC SNPs have been associated with HDL-C levels (Table 1) (Andersen et al, 2003;Costanza et al, 2005;de Andrade et al, 2004;Fang and Liu, 2002;Grarup et al, 2008;Iijima et al, 2008;Isaacs et al, 2007;Kathiresan et al, 2008b;Ko et al, 2004;McCaskie et al, 2006;Nettleton et al, 2007;Tai et al, 2003a;Talmud et al, 2002b;Whiting et al, 2005;Yamada et al, 2007). However, the most consistent associations have been observed for rs1800588 and rs2070895 and, several SNPs in the promoter region are in strong LD (Boes et al, 2009).…”
Section: Genetic Variation In Enzymes Involved In Lipid Metabolism Anmentioning
confidence: 89%
See 1 more Smart Citation
“…The human HL/LIPC gene is located on chromosome 15 (15q21). Several HL/LIPC SNPs have been associated with HDL-C levels (Table 1) (Andersen et al, 2003;Costanza et al, 2005;de Andrade et al, 2004;Fang and Liu, 2002;Grarup et al, 2008;Iijima et al, 2008;Isaacs et al, 2007;Kathiresan et al, 2008b;Ko et al, 2004;McCaskie et al, 2006;Nettleton et al, 2007;Tai et al, 2003a;Talmud et al, 2002b;Whiting et al, 2005;Yamada et al, 2007). However, the most consistent associations have been observed for rs1800588 and rs2070895 and, several SNPs in the promoter region are in strong LD (Boes et al, 2009).…”
Section: Genetic Variation In Enzymes Involved In Lipid Metabolism Anmentioning
confidence: 89%
“…The human LPL gene is located on chromosome 8 (8p22). Several LPL SNPs have been associated with HDL-C (Table 1) (Ahn et al, 1993;Corella et al, 2002;Holmer et al, 2000;Klos and Kullo, 2007;Klos et al, 2006;Komurcu-Bayrak et al, 2007;Lee et al, 2004;Nettleton et al, 2007;Senti et al, 2001;Wittrup et al, 1999); however, many of them are in strong linkage disequilibrium with each other (e.g., rs320, rs326, rs13702, rs10105606) (Boes et al, 2009;Heid et al, 2008). Hepatic lipase (HL; LIPC) is a glycoprotein that is synthesized by liver cells (hepatocytes) and catalyzes the hydrolysis of TG and phospholipids (Miller et al, 2003).…”
Section: Genetic Variation In Enzymes Involved In Lipid Metabolism Anmentioning
confidence: 99%
“…Nettleton et al 31 showed that white and African-American adults with the CG/GG genotype had higher HDL-C and lower TG concentrations than their counterparts. This profile is generally associated with reduced risk of CVD.…”
Section: Discussionmentioning
confidence: 99%
“…S447X polymorphism affects postprandial lipemia, and this may be a mechanism for its effects on TG and HDL-C concentrations. 31 However, the mechanism for the effects of this polymorphism on serum lipid metabolism remains obscure. One study suggested that S447X polymorphism might alter LPL translation, 33 but its mechanism is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Nettleton et al, (2007) carried out a study in 11,806 (8897 Whites/ 2909 African Americans) participating in the Atherosclerosis Risk in Communities (ARIC) study. This study consisted of a cohort of men and women, aged 45-64, from four communities in the United States (Forsyth County, North Carolina; Jackson, Mississippi; Northwest Minneapolis suburbs, Minnesota; Washington County, Maryland).…”
Section: Hepatic Lipase Gene Variation and Total Fat Intake In Determmentioning
confidence: 99%